2020
DOI: 10.1007/s00167-020-06354-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and contemporary diagnoses for lateral hip pain: a scoping review

Abstract: Purpose Recent advances in diagnostic imaging techniques and soft tissue endoscopy now allow for precise diagnosis and management of extra-articular hip pathology. The aim of this scoping review is to present an evidence-based update of the relevant literature focussing only on the pathoanatomy, clinical assessment and the diagnosis of pathology in the peritrochanteric space. Methods A literature search was performed on PubMed to include articles which rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…A full-thickness tear of the gluteus medius tendon is a common cause of pain with limping and functional limitation [ 28 ], and surgery is recommended in case of failure of non-operative management [ 12 ]. For the first time, the clinical outcomes of this novel surgical procedure combining endoscopic gluteus medius repair with the release of gluteus maximus reflected tendon and medium- and long-term follow-ups have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A full-thickness tear of the gluteus medius tendon is a common cause of pain with limping and functional limitation [ 28 ], and surgery is recommended in case of failure of non-operative management [ 12 ]. For the first time, the clinical outcomes of this novel surgical procedure combining endoscopic gluteus medius repair with the release of gluteus maximus reflected tendon and medium- and long-term follow-ups have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although trochanteric pain is generally associated with the inflammation of the trochanteric bursa, many studies have suggested that the main cause of lateral hip pain is tearing in gluteal muscles, which is more prevalent in gluteus medius than in gluteus minimus [ 3 , 28 ]. Abductor tears are characterised more often by the onset of chronic pain generated by attritional forces than by acute traumatic pain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this test only reached a sensitivity of 72.7% and a specificity of 76.9%. Multiple other studies have shown the utility of Trendelenburg's sign to identify gluteal tendinopathy, but the test alone cannot diagnose abductor tendon tears as it is seen in many other pathologies including superior gluteal nerve palsy, Legg-Calve-Perthes disease, osteonecrosis of the hip, and DDH 13,22,[27][28][29] . Ultimately, patients who have these symptoms as summarized in Table II and continue to have refractory pain after nonoperative management should be considered for advanced imaging.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Snapping hip is an extra‐articular phenomenon involving movements of a tendon over a bony relief. External snapping hip (ESH), occurring in the lateral peri‐trochanteric area, arises due to an abrupt movement of the iliotibial band (ITB) over the great trochanter (GT) and is enhanced by a thickening of the posterior part of the ITB or the anterior margin of the gluteus maximus muscle [19, 21]. ESH usually affects young adults, mostly female, practicing sports with repetitive hip motions such as football, dance, martial arts or running [21].…”
Section: Introductionmentioning
confidence: 99%